Direct observation of cargo transfer from HDL particles to the plasma membrane. (October 2018) - Plochberger, Birgit; Axmann, Markus; Röhrl, Clemens; Weghuber, Julian; Brameshuber, Mario; Rossboth, Benedikt K.; Mayr, Sandra; Ros, Robert; Bittman, Robert; Stangl, Herbert; Schütz, Gerhard J.
Abstract: Background and aims: Exchange of cholesterol between high-density lipoprotein (HDL) particles and cells is a key process for maintaining cellular cholesterol homeostasis. Recently, we have shown that amphiphilic cargo derived from HDL can be transferred directly to lipid bilayers. Here we pursued this work using a fluorescence-based method to directly follow cargo transfer from HDL particles to the cell membrane. Methods: HDL was either immobilized on surfaces or added directly to cells, while transfer of fluorescent cargo was visualized via fluorescence imaging. Results: In Chinese hamster ovary (CHO) cells expressing the scavenger receptor class B type 1 (SR-B1), transfer of amphiphilic cargo from HDL particles to the plasma membrane was observed immediately after contact, whereas hydrophobic cargo remained associated with the particles; about 60% of the amphiphilic cargo of surface-bound HDL was transferred to the plasma membrane. Essentially no cargo transfer was observed in cells with low endogenous SR-B1 expression. Interestingly, transfer of fluorescently-labeled cholesterol was also facilitated by using an artificial linker to bind HDL to the cell surface. Conclusions: Our data hence indicate that the tethering function of SR-B1 is sufficient for efficient transfer of free cholesterol to the plasma membrane. Graphical abstract: Image 1 Highlights: Transfer of amphiphilic cargo from HDL to the plasma membrane occurs immediately after contact. Tethering function of SR-B1 is sufficient for efficient transfer of free cholesterol. After HDL is captured, SR-B1 is dispensable for the cargo transfer process itself.